Animals as sentient beings in the Political Constitution of Mexico City - Krizia Said Castagno (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
Mexico City recognizes in its Constitution that animals are sentient beings and therefore they deserve protection and good treatment.